Una teoria oggettiva del benessere animale. La giustizia interspecifica di Nussbaum - Guma, Francesca (Filosofia Morale/Moral Philosophy, 2022)
Many authors have spoken about the importance of recognizing a moral status to non-human animals, emphasizing the need to change – even radically – the treatment given to other species. For Nussbaum it is a question of justice: it is necessary to go beyond compassion and humanity, beyond the species barrier, proposing a theoretical model that considers the dignity of non-human animals. In this perspective, Nussbaum extends her capabilities approach in an interspecies sense, with the aim of ensuring fundamental moral entitlements to non-human animals, as well as making it possible for them to have a good life. However, the proposal shows ambiguities and tensions that are not congruous with the foundations of the capabilities approach. Nussbaum’s theoretical difficulties appear incompatible with her idea of going beyond compassion and humanity to achieve interspecies justice.